The Effect of The Sequential Whispering Game on Listening Skill Teaching for Islamic Junior High School Students in Indonesia/أثر لعبة الهمس المتسلسل على تعليم مهارة الاستماع لدى طلاب المدرسة المتوسطة الإسلامية بتانجيرانج الجنوبية - Albantani, Azkia Muharom; Muhammad, Mohd Zulfahmi; Fauziah, Afwa Uzna (UIN ANTASARI, 2022)
The researcher chose this title because of problems in listening skills learning activities, such as students have not been able to receive information or messages contained from a speaker, which is caused by a lack of vocabulary,their inability to differentiate short and long sounds of letters in pairs.In addition, the students lack interest in learning, and the teacher chooses media and methods unsuitable for listening learning activities. This study aims to analyze the application of chain whispering games in teaching listening, analyze the effect of chain whispering on students' learning outcomes, and reveal the supporting and inhibiting factors in teaching this game. This quantitative research uses an experimental (pre-experimental) method with a one-group pretest-posttest design. The population in this study were students of class VIII at MTs Serpong, and researchers took research samples of 33 students in class VIII. Researchers used data collecting methods: pre- and post-tests, observation, interviews, and questionnaires. After the researcher gave the pretest and posttest to students, this study obtained an average pretest score of 53.48 and an average posttest score of 79.10, with the results of the effectiveness of the N-Gain pretest and posttest of language games on students' listening skills was 54.0 with the category enough. After the calculation, the table value is obtained at the 5% level, which is 0.943, and shows that the Zero Hypothesis ( 16HO